Cognitive - Linguistic Profiling of a Young Male with a Craniopharyngioma - Georgiou, Myrianthi (Τμήμα Επιστημών Αποκατάστασης, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2019)
The goal of this case study is to present the cognitive-linguistic profile of a 19 year old male (D.D.) with a craniopharyngioma diagnosis, after he underwent surgery for the removal of the tumour. Both the cognitive and language performance of the participant have been recorded using a total of ten (10) different assessment tools: the Boston Diagnostic Aphasia Examination-Short Form, the Compound Word Test, the Test of Idioms and Metaphors, the LITMUS-Multilingual Assessment Instrument of Narratives, the Grammar Decision Test, the LITMUS-Sentence Repetition Task, the RehaCom Software, the Wechsler Adult Intelligence Scale III, the Non-Word Repetition Task, and the Raven’s Coloured Progressive Matrices. The results revealed that the main difficulties are part of the cognitive domain, with working memory to be demonstrated as the most problematic. Most of the language skills that were assessed are intact, but difficulties linked to the semantic network, (e.g. the comprehension of metaphors and idioms), were recorded. There is limited information in the literature about the language skills of people with craniopharyngioma, therefore this study aims to contribute to the development of knowledge on this topic.
Keywords: Case study; Cognitive-linguistic profile; Craniopharyngioma; Assessment tools; Working memory; Comprehension; Metaphors and idioms